O museu escolar do CEAP: reflexões sobre a prática museal e a relação entre memória e história - Borcioni, Leonardo (2012)
This Master’s thesis addresses the cultural institution “School Museum of the Evangelical School Augusto Pestana”, in Ijuí, founded in 1973, from a study on the constitution of a social memory of a cultural group with ethnic connotations. From theoretical references such as memory and ethnicity, this study discusses concepts regarding their historical and cultural dimensions, i.e., the way in which this cultural group of Teutonic Evangelicals in Ijuí produces discursive strategies of belonging to a particular ethnic segment through a posture of preservation of a historic past, as a strategy of resistance to acculturation in a context marked by multiculturalism and loss of traditional cultural references in a culturally dynamic society. Through a policy of heritage preservation, gathered at the school museum mentioned, it is possible to observe how Teutonic Evangelicals in Ijuí use discourses of belonging related to the evangelical community of Ijuí and to a transnational German community, supposedly imaginary, as a way of differentiation between this and other local cultural groups, establishing a hierarchy among their group, based on the authority and legitimacy of a particular historic discourse. This work aims to understand how such strategies and discourses of belonging to a distinct cultural group of ethnic connotations recurs to an ideological and political strategy that uses a history that is being constantly updated and adapted to a local and particularized context.